A DFT STUDY ON THE PHONON PROPERTIES OF PEROVSKITES ASnCl3 (A = K, Rb, AND Cs) - Russell Ong; Dinda Fadhilah Nur Azimmi (Universitas Negeri Medan, 2026)
Inorganic perovskites such as ASnCl3 (A = K, Rb, and Cs) are widely used in solar cells because they are known to have many advantages, such as being easily obtainable and having high efficiency. Therefore, in this study, we conducted computational study to determine the phonon properties of ASnCl3 perovskites (A = K, Rb, and Cl) with a pm3m space group in a bulk system. These properties were calculated using density functional theory (DFT) through the Quantum ESPRESSO program. The phonon properties discussed are phonon density of states (PHDOS) and phonon dispersion. In addition, the dielectric constant was also calculated because the code is straightfoward in the dynamical matrix process. To calculate the phonon properties, the optimum lattice constant must be achieved through k-point optimization and kinetic energy cut-off. The results show that the highest phonon distribution in KSnCl3, RbSnCl3, and ClSnCl3 perovskites is at frequencies of -68.52 cm-1, -55.37 cm-1, and 55.83 cm-1, respectively. The presence of phonon distribution or phonon dispersion curves at negative frequencies explains that ASnCl3 perovskites (A = K, Rb, and Cl) are unstable perovskites. Nevertheless, the dielectric constants of these three perovskites are quite good, making them very promising as active materials for perovskite solar cells. When compared to the reference static dielectric constants, the obtained values are consistent with the Lyddane‒Sachs‒Teller relation.